Low-profile Power Adapter Based on a Resonant LCC Converter - Pawellek, Alexander (IEEE International Symposium on Industrial Electronics (ISIE 2010), 2010)
In addition to high efficiency of switch mode power supplies, miniaturization of converters is an increasingly important aspect. In order to meet safety regulations as well as the design goal of flatness, complicated integrated magnetics are proposed in literature. Unfortunately, their design is difficult and the costs of these components are rather high. This paper focuses on the resonant LCC converter with capacitive output filter, which is a promising topology with respect to low-profile designs. The transformer necessary for mains isolation is realized on a ring core, thus regulation requirements are combined with a low-cost magnetic component. The exact analysis of the LCC converter in the time domain is presented and the solutions of the four important modes of the converter are derived. A prototype was designed in order to demonstrate the feasibility of the proposed approach with an application scenario typical for notebook adapters. © 2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.lselek.lowpro